INDUSTRIAL WASTE MANAGEMENT AND TOXIC EFFECTS ON THE ENVIRONMENT AND HUMAN HEALTH - Camelia Căpăţînă; Ramona Violeta Cazalbașu (Fiabilitate şi Durabilitate)
The concept of sustainable development became a strategic objective for all mankind, it includes the idea of human development and it ensures continuity, without depletion beyond the affordability and regeneration of ecosystems. The waste is remnants of various natures (organic, inorganic, solid, liquid, gaseous, etc.) resulting from various industrial processes, agricultural activities, street, railway or water transport, household activities and housework. In accordance with art. 1 - Directive 75/442 C.E. of 15. 07. 1975 it is considered as waste any substance or object whose holder discards, intends or is required to throw. Regardless the action to be taken, a final waste will remain in the last stage of waste decomposition.